2017
DOI: 10.1111/ped.13377
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study for brain/body hypothermia for hypoxic–ischemic encephalopathy: Changes inHMGB‐1

Abstract: In HIE, HMGB-1 differs according to the presence of BHT, suggesting that HMGB-1 measurement soon after birth might be useful for determining BHT necessity and short-term outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
(65 reference statements)
1
5
0
Order By: Relevance
“…We have confirmed and reported in a multicenter cohort study that the effectiveness of brain hypothermia in neonatal asphyxia can be judged by changes in the serum high mobility group box-1 (HMGB-1) concentration [5]. Furthermore, we observed the serial changes of HMGB-1 in the blood of infants who had already developed fetal asphyxia and suffered severe sequelae even though brain hypothermia was started within 6 hours after birth.…”
Section: Introductionsupporting
confidence: 79%
“…We have confirmed and reported in a multicenter cohort study that the effectiveness of brain hypothermia in neonatal asphyxia can be judged by changes in the serum high mobility group box-1 (HMGB-1) concentration [5]. Furthermore, we observed the serial changes of HMGB-1 in the blood of infants who had already developed fetal asphyxia and suffered severe sequelae even though brain hypothermia was started within 6 hours after birth.…”
Section: Introductionsupporting
confidence: 79%
“…Studies have shown that therapeutic hypothermia in neonatal HIE is effective to prevent long-term neurodevelopmental consequences [7][8][9][10][11] and results in fewer effects of organic injuries in newborns [7][8][9][10]. Although therapeutic hypothermia is used clinically to reduce neurological injury secondary to HIE, there remains a 45-55% risk of death or moderate to severe disability in treated infants [7,8,10].…”
Section: Benificial Effects Of Therapeutic Hypothermia Therapymentioning
confidence: 99%
“…The potential benefit of therapeutic hypothermia has increased pressure on clinicians to promptly and accurately assess neonatal HIE and the severity of the encephalopathy that may result [15]. Hypothermia therapy was also shown to improve function in organs other than the brain [7][8][9][10][11]16], exhibited lower mortality during first hospitalization [16], and lower hearing impairment in the hypothermia group compared with control infants [7,16].…”
Section: Benificial Effects Of Therapeutic Hypothermia Therapymentioning
confidence: 99%
“…Hypothermia as a rescue therapy for neonatal HIE is proven to be effective and to result in few adverse effects in newborns [ 5 , 6 , 7 ]. Although therapeutic hypothermia is employed to reduce neurological injury caused by HIE, a 45–55% risk of death or moderate or severe disability in treated infants remains [ 5 , 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%